Genetic Characterization and Fruit Quality Analysis of New Mandarin Hybrids - Cristofani-Yaly, Mariângela; Dezotti, Ana Lúcia; Cavichioli, Thaís Magni [UNESP]; Roverssi, Fernanda; Novelli, Valdenice Moreira; Bastianel, Marinês (MDPI, 2024)
Mandarin fruits with good physicochemical quality are desired for the fresh fruit market. The ease of crosses among citrus taxa has been used to expand genetic variability and select new varieties for different fruit markets. With the aim of selecting new commercial varieties, eleven hybrids obtained from the cross between Murcott tangor and Ponkan mandarin were grafted on Rangpur lime rootstock and evaluated for genetic and phenotypical characteristics. It was observed that there are significant differences in the fruit shape, content, and organoleptic characteristics in juice and differential responses to Alternaria alternate, the causal agent of the Alternaria brown spot (ABS) disease. The phenotypic and molecular characterization showed two groups of hybrids, those that resemble Ponkan and others with characteristics closer to the parental Murcott. There are significant differences in the period of fruit maturation among the hybrids and their parents. Considering the parents stand out as the main commercial varieties in the Brazilian mandarin fresh fruit market, these new hybrids have great potential for commercial acceptance and could be an excellent option to extend the period of supply of mandarins. Genetic and phenotypical information will be fundamental for the registration and/or protection of new varieties, which are essential steps that precede the commercial release to the producer.
Keywords: Alternaria alternata; genetic diversity; molecular markers